PENGARUH JENIS PEGANGAN TERHADAP HASIL AKURASI GATING PADA WOODBALL - Lumbanraja, Elva Selfiana (Journal of Sport Coaching and Physical Education, 2016)
Gating is an important hit in woodball game to complete each fairway. Grip technique is a factor that affects the gating accuracy. The problem in this research is to define any influence of training using baseball grip and baseball finger straight grip to the gating accuracy results and which one better training is.This is an experimental study. The population of the study is a member of UKM Woodball Unnes 2016 with a sample of 16 people using purposive sampling technique. The independent variable of this research is training uses baseball grip and training uses baseball finger straight grip while the dependent variable is gating accuracy results.